Discourse Analysis on the Statement of the Minister of Religious Affairs Concerning "Good-Looking Radicalism” against State Civil Apparatus - Ulfa, Fania Zakiyah; Cahyani, Ida Fitria; Arif, Rozaqul (Proceedings of International Conference on Da'wa and Communication, 2020)
This study aims to describe the discourse of the Minister of Religion's statement regarding good-looking radicalism among the State Civil Apparatus. This study uses a descriptive qualitative method with van Djik's critical discourse analysis. The data collection uses documentary techniques from Youtube video webinars and a number of journals. The macrostructure shows that there are strategies that can be done to ward off the entry of radical ideology in ASN. The superstructure shows the process of radicalism agents entering through educational institutions and houses of worship with an attractive appearance to deceive the public. The microstructure analysis shows that this statement of good-looking radicalism has generated polemic in society because it is subjective, that is, it cannot be generalized based on one case. The result of this study shows that some people think that the Minister of Religion agrees with the good-looking radicalism movement. The communicator is the Minister, namely as a messenger to ward off radicalism agents by being careful in selecting ASN. The Minister has access to convey messages to the public to be aware of the entry of radical-minded people into mosques, which usually starts from people who are good-looking, speak Arabic well, and have sufficient religious knowledge.